2016
DOI: 10.1007/s12272-016-0731-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolism of honokiol in mouse, rat, dog, monkey, and human hepatocytes

Abstract: Honokiol has antitumor, antioxidative, anti-inflammatory, and antithrombotic effects. Here we aimed to identify the metabolic profile of honokiol in mouse, rat, dog, monkey, and human hepatocytes and to characterize the enzymes responsible for the glucuronidation and sulfation of honokiol. Honokiol had a high hepatic extraction ratio in all five species, indicating that it was extensively metabolized. A total of 32 metabolites, including 17 common and 15 different metabolites, produced via glucuronidation, sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Therefore, it is necessary to understand the metabolic pathway of 25B-NBF in order to develop a bioanalytical method for monitoring 25B-NBF abuse. The purposes of this study were to identify in vitro metabolic profiles of 25B-NBF using human hepatocytes, the gold standard in vitro metabolism model, and liquid chromatography–high resolution mass spectrometry (LC–HRMS) [17,18,19] and to characterize the specific cytochrome P450 (CYP) and uridine 5′-diphospho-glucuronosyltransferase (UGT) enzymes responsible for 25B-NBF metabolism using human cDNA-expressed CYPs and UGTs in order to predict the pharmacokinetics and drug-interaction potential of 25B-NBF.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to understand the metabolic pathway of 25B-NBF in order to develop a bioanalytical method for monitoring 25B-NBF abuse. The purposes of this study were to identify in vitro metabolic profiles of 25B-NBF using human hepatocytes, the gold standard in vitro metabolism model, and liquid chromatography–high resolution mass spectrometry (LC–HRMS) [17,18,19] and to characterize the specific cytochrome P450 (CYP) and uridine 5′-diphospho-glucuronosyltransferase (UGT) enzymes responsible for 25B-NBF metabolism using human cDNA-expressed CYPs and UGTs in order to predict the pharmacokinetics and drug-interaction potential of 25B-NBF.…”
Section: Introductionmentioning
confidence: 99%
“…Cryopreserved human hepatocytes were purified and recovered using a high-viability cryohepatocyte recovery kit according to the manufacturer′s protocol. Purified human hepatocytes were resuspended in William′s E buffer to a final density of 0.8 × 10 6 cells/mL [ 16 ]. A portion of the human hepatocyte suspension (62.5 μL; 5 × 10 4 cells) and 62.5 μL of 400 μM verproside were added to a 96-well plate and incubated for 2 h at 37 °C in a CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolite identification and characterization of the enzymes responsible for the metabolism of drugs, such as cytochrome P450, UDP-glucuronosyltransferase (UGT), and sulfotransferase (SULT), can reveal potential drug–drug interactions and inter-individual variations in drug metabolism and pharmacokinetics [ 14 , 15 , 16 ]. It is important to establish the comparative metabolism and drug-metabolizing enzymes of verproside for a full characterization of its pharmacokinetics, pharmacodynamics, and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…A recent in vitro study identified the metabolic profile of honokiol in different animal species and the enzymes involved in its derivatization. The neolignan was extensively metabolized by extrahepatic and hepatic pathways, producing glucuronic derivatives as main compounds and other 32 metabolites after sulfation and oxidation [32]. Human metabolism usually employs conjugation with glucuronic acid in order to increase compoundsʼ hydrophilic properties, facilitating their excretion.…”
Section: Regionmentioning
confidence: 99%
“…Liver and intestine are the two most important glucuronidation sites for orally administered neolignans. It has been reported that magnolol and honokiol can potently inhibit the activity of UGT isoforms 1A7 and 1A9 in humans and rodents [32,51]. This is not a trivial matter, since UGTs exert an important protective effect against many carcinogens and drugs with side or ▶ even toxic effects, and their inhibition slows the clearance of drugs, thus raising their blood and tissue levels.…”
Section: Interaction With Drugs or Other Substancesmentioning
confidence: 99%